FILIAL PIETY CONTAINED IN FACE THREATENING ACTS IN DORAEMON AND KOBO CHAN: A MANGA ANALYSIS - Theresia Arianti; Neni Nurkhamidah (English Education Department at FKIP Nommensen University, 2023)
Filial Piety is a value rooted form Confucianism. This value demands one to respect parents. As this value spreads widely in East Asia, this study aims to investigate what filial piety values contained in Doraemon and Kobo Chan, and to examine which same filial piety values shared in both comic books. Doraemon and Kobo Chan are chosen since these two comic books are originated from Japan whose society adopts filial piety. These two comic books are important to be studied since the two were highly popular in Indonesia in the late 1990’s and early 2000’s and were enjoyed by many Indonesian children. This study found that acquiescent respect and care respect are two values having the highest numbers of appearances in Doraemon and Kobo Chan, respectively. While the values contained in both comic books are acquiescent respect and respecting the ancestors. It is hoped that future studies could examine the relation between these values contained in both comic books and Indonesia’s young generation’s decision to take a role as a sandwich generation.